2024
DOI: 10.1186/s12876-024-03230-x
|View full text |Cite
|
Sign up to set email alerts
|

Fructose malabsorption and fructan malabsorption are associated in patients with irritable bowel syndrome

Twan Sia,
Riki O. Tanaka,
Albert Mousad
et al.

Abstract: Background Food malabsorption and intolerance is implicated in gastrointestinal symptoms among patients with irritable bowel syndrome (IBS). Key triggers include fructose and fructan. Prior studies examined fructose and fructan malabsorption separately in IBS patients. None have concurrently assessed both within the same patient group. We aimed to investigate the association between fructose and fructan malabsorption in the same patients with IBS using hydrogen breath testing (HBT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
0
0
Order By: Relevance
“…Chumpitazi et al found that fructans exacerbated symptoms in a selected group of children with IBS [29]. This was also reported in studies in adults with IBS [30,31]. Interestingly, our study conducted on a population of children who were not previously diagnosed with IBS, also found that fructan-rich vegetables, particularly onions and garlic, were prevalent food items associated with GI symptoms-in particular, abdominal pain, nausea, and flatulence.…”
Section: Discussionsupporting
confidence: 85%
“…Chumpitazi et al found that fructans exacerbated symptoms in a selected group of children with IBS [29]. This was also reported in studies in adults with IBS [30,31]. Interestingly, our study conducted on a population of children who were not previously diagnosed with IBS, also found that fructan-rich vegetables, particularly onions and garlic, were prevalent food items associated with GI symptoms-in particular, abdominal pain, nausea, and flatulence.…”
Section: Discussionsupporting
confidence: 85%